Zwischendurch mal ... Spiele Kopiervorlagen A1-B1 - Beck, Carmen; Duckstein, Barbara; Hagner, Valeska; Hawerlant, Andrea; Heuer, Wiebke; Luyken, Michaela; Schümann, Anja (Ismaning : Hueber Verlag, 2007)
50 Kopiervorlagen mit Spielen zu Grammatik, Wortschatz, Syntax u.v.m.